The Effectiveness of Using E-Learning as an Online Learning Media at Polytechnic Indonusa Surakarta - Suci Purwandari; Edy Susena (International Journal of Computer and Information System (IJCIS), 2022)
The Covid-19 outbreak has had a tremendous effect in no time. The Minister of Education and Culture of the Republic of Indonesia has adopted a policy to protect the nation's children from studying at home by means of distance education. Various technology platforms can be used to assist in the learning process. PJJ is e-learning-based learning. Indonusa Surakarta Polytechnic seeks to improve campus e-learning performance. To increase the use of e-learning, it is necessary to evaluate the use of campus E-Learning as an online learning medium at the Polytechnic Indonusa Surakarta. For a good evaluation, researchers conduct research in order to get feedback from users. The intended users are lecturers and students. The researcher used a qualitative descriptive method and the collection was done by means of a literature study and a questionnaire. The questionnaire used a linkert 4 scale, namely a 4 linkert scale questionnaire, namely Strongly Agree (Score 4), Agree (Score 3), Disagree (Score 2) and Disagree (Score 1). The methodology carried out begins with the formulation of the problem, data collection. The results of data collection were carried out by descriptive analysis so as to produce accurate conclusions. The conclusions of this study are: 67.2% of respondents agree during the pandemic and future online learning, 68.6% of respondents agree that lectures use the campus e-learning platform, 71.4% of respondents agree that campus e-learning is easy to use, 65 % of respondents agree that campus e-learning can facilitate learning between lecturers and students, 58.9% of respondents agree that campus e-learning can improve student competence, 90.2% of respondents agree that lectures use books/modules as lecture references, references in the form of printed books (59.4%) and E-Books (56.7%), The use of online learning platforms other than Campus E-Learning include: Zoom (56.3%), Gmeet (86.5%), Google Classroom (82, 5%), WhatsApp Group (71.9%), E-mail (36.5%) and others (9.4%)